Mengungkap Peran Komunikasi Tim dalam Meningkatkan Efektivitas Tim: Literature Review - Sumiok, Maisye Angelina; Ari Rifaldi; Laila Nur Aisah; Aly Al Rasyid; Najwa Diani Pajriyanti; Rafli Putra Pratama; Ridlwan Muttaqin (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2026)
Team communication is a crucial element that serves as the main foundation in shaping team effectiveness across various organizational contexts, ranging from conventional work teams to virtual teams in the digital era. This literature Review reveals the role of team communication through an in-depth analysis of 20 peer-Reviewed scientific journals from national and international sources published between 2015 and 2024. This approach highlights how effective communication not only facilitates information exchange but also builds trust, cohesion, and optimal team performance. Specifically, this Review discusses the definition of team communication, its main objectives such as task coordination and conflict resolution, its benefits including increased productivity and innovation, common barriers such as cultural differences and technological limitations, as well as improvement strategies such as the use of digital tools and psychological safety training. The results show that well-managed team communication can significantly enhance team effectiveness based on findings from various studies. Practical implications include recommendations for managers to integrate communication as a strategic priority, while future research suggestions focus on the context of post-pandemic hybrid teams.